Development and Evaluation of a Blockchain-Based Financial Audit Tracking System for Mobile Platforms - Liu, Eying (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rapid development of blockchain technology, its applications in finance, supply chains, and auditing have garnered widespread attention. Traditional financial auditing faces challenges such as data tampering, audit opacity, and difficulties in traceability, necessitating the development of more efficient, secure, and transparent auditing methods. Blockchain technology, with its decentralized, tamper-resistant, and fully traceable characteristics, has emerged as a powerful tool for addressing the challenges inherent in traditional auditing practices. Especially in the context of the growing prevalence of mobile platforms, the integration of blockchain technology with financial audit tracking systems can not only enhance transparency throughout the auditing process but also significantly improve audit efficiency. However, existing research has primarily focused on the basic applications of blockchain technology, with limited analysis of mobile platform requirements and comprehensive integration of blockchain with audit information tracking mechanisms. In response to this gap, a blockchain-based financial audit tracking system was proposed and developed, comprising two core elements: firstly, a layered structure for the blockchain system that is tailored for mobile platforms, ensuring both security and efficiency; secondly, the implementation of a tracking mechanism for financial audit data, enabling transparent tracking and validation of the entire auditing process via blockchain technology. The results indicate that the system effectively addresses issues such as information tampering, data loss, and audit opacity in traditional financial auditing, providing a safer, more transparent, and efficient solution for financial audits.